The Value of Local Wisdom Managing Natural Resources in Lake Toba as a Source of Learning Geography - Saragih, Lenda Janed; Somantri, Lili; Yani, Ahmad (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The purposes of this study are: 1) to know the value of local wisdom and knowledge of the community in preserving natural resources in the Lake Toba area; and 2) making local wisdom of Batak community in the Lake Toba area as a learning source of geography. The method used in this study is descriptive qualitative. The source of data is obtained by observing and interviewing in Batak Toba indigenous peoples. The local wisdom values of Toba tribe in preserving the Lake Toba area are religious or spiritual, environmental care, mutual cooperation, creative, responsible and consistent. The inheritance of local wisdom occurs through an enculturation process in informal education and government socialization in managing Lake Toba. The results of this study recommend that local wisdom can be used as a learning source of geography, namely the material for sustainable natural resource management